2021
DOI: 10.1155/2021/3295021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bloodletting at Shaoshang and Shangyang Acupuncture Points on Outcome and Prognosis of Severe Community-Acquired Pneumonia in the Elderly

Abstract: Objectives. The aim of this study was to explore, whether treatment with bloodletting at Shaoshang and Shangyang acupuncture points would affect therapy outcome and prognosis for severe community-acquired pneumonia (SCAP) in the elderly. Methods. A total of 62 patients, who met the diagnostic criteria for SCAP, were enrolled in the study and randomly divided into two groups, i.e., treatment group ( n = 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A previous study demonstrated that needle bloodletting at LU 11 improved the symptoms of pneumonia. [51] Another study demonstrated that acupuncture at LU 11 blocked the infiltration of CD4 + T cells and inflammatory cells to regulate inflammation. [52] In addition, several studies have confirmed the local antinociceptive effect of acupuncture, thereby supporting local acupuncture in the throat.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that needle bloodletting at LU 11 improved the symptoms of pneumonia. [51] Another study demonstrated that acupuncture at LU 11 blocked the infiltration of CD4 + T cells and inflammatory cells to regulate inflammation. [52] In addition, several studies have confirmed the local antinociceptive effect of acupuncture, thereby supporting local acupuncture in the throat.…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed as a superiority trial with a level of significance set at α=0.05, a type II error (β) of 0.2 and a power of the test of 80%. The sample size was calculated based on similar studies,7 with a 1:1 ratio between the intervention and control groups, and a dropout rate of 15% was considered. 66 patients with SP will be assigned to either intervention or control group and will undergo assessments on the 1st, 5th and 10th days of the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Infections caused by pathogenic bacteria are threatening human beings' health worldwide [1]. These bacteria are easily to develop drug resistance during antibiotics treatment processes [2]. Once obtained resistance, bacteria are often difficult to eradicate by antibiotics [3].…”
Section: Introductionmentioning
confidence: 99%